Ovariectomy reduces the risk of tumour development and influences the histologic continuum in canine mammary tumours. (23rd December 2021) - Gedon, Julia; Wehrend, Axel; Kessler, Martin
Abstract: Influence of neutering on canine mammary tumorigenesis has been a source of vivid discussion over the last decades. The purpose of this retrospective study was to describe the association between neuter status, tumour size and degree of malignancy in a large population of 625 female dogs with altogether 1459 removed mammary tumours (MTs). MT‐bearing dogs were predominantly intact (80.3%) and intact dogs were overrepresented in the tumour population compared to the control group of >19 000 females ( p < .0001). Multiple MT occurred in 340 patients (54.4%) and were significantly more common in intact dogs (57.8% vs. 40.7% spayed). Neutered dogs were not only significantly more likely to have a malignant MT ( p < .0001) but were significantly more often affected by more aggressive tumour subtypes ( p < .0001). Positive correlation between increasing tumour size and increasingly malignant phenotype was slightly stronger in spayed ( r s = .217; p = .021) compared to intact ( r s = .179; p = .0003) patients. After ovariectomy, progression from benign to malignant occurs in smaller size tumours, as MT ≥2 cm in diameter were malignant in 86.9% of the spayed patients, compared to 62.0% in intact patients ( p = .0002). Intact bitches have a higher risk for MTs and tumour multiplicity. MTs in neutered females are more often malignant and belong to more aggressive subtypes compared to MTs in intact dogs. In neutered bitches, histologic progression from benign to malignant and further along the cancer progression continuum occurs at smaller tumour sizes.